Eco-phytosociology method and it new application in determination and discrimination of Intraspecific Diversity, case study: Astragalus verus and Astragalus glaucops (Global Journal of Science Frontier Research, 2012)
This study carried out for determination and discrimination of intraspecific diversity of Astragalus verus and Astragalus glaucops by Eco-phytosociological method from west of Iran. In this order, application of Endogenous milieu (special station) for data collecting and then their analyzing permit us only determine existence of inter and intraspecific diversity. Then for determinating kind and level of intraspecific diversity (Ecophene, Chemotype, Cytotype, Ecotype ...), can use other studies such as: morphological, anatomical, phytochemical, cytological and etc. In this survey, 31 special stations were studied. Then floristic-ecologic data collected from each 31 special stations and analyzed by Anaphyto software (F.C.A, A.H.C, Marquag methods). Comparison of obtained results on multiple coordinate axes from F.C.A method with results from Marquag and A.H.C methods led to determination of 7 main groups of Endogenous milieus (special station). Flavonoid analyses were used for determination kind and level of intraspecific diversity in 7 discriminated groups. Leaves flavonoid components of all collected individuals of Astragalus verus and Astragalus glaucops were investigated by TLC method. Obtained data from flavonoid survey analyzed by MVSP package with WARD and UPGMA methods. Finally, the results of flavonoid studies confirmed the same groups that identified by floristical composition study and showed intraspecific diversity in chemotype level.
Keywords: Astragalus verus; Astragalus glaucops; Eco-phytosociology method; intraspecific diversity